Numerical simulation of temperature distribution of heat flow on reservoir tanks connected in a series - Kazeem Iyanda, Falade; Rezazadeh, Hadi; Inc, Mustafa; Akgül, Ali; Mujitaba Bashiru, Ibrahim; Bilal Hafeez, Muhammad; Krawczuk, Marek (Alexandria engineering journal, 2023)
The flow of temperature distribution through a medium in thermodynamic studies plays an important role in understanding physical phenomena in chemical science and petroleum engineering, while temperature distribution indicates the degree of reaction that must be undergone to obtain the final product. Therefore, this paper aims to present and apply the exponential matrix algorithm (EMA), differential transformation algorithm (DTA), and Runge-Kutta (RK5) to simulate the temperature distribution in five heating tanks in series. successive preheating of multicomponent oil solutions. A mathematical model of the energy balance equations of the reservoir is considered. Two computer experiments were performed to test and investigate the relationship between two constant parameters appearing in the model. Numerical simulation of saturated steam Tsteam temperature of 500 °C and 1000 °C used to heat the tanks and initial temperature T035°Cand100°C of the first tank feed oil are considered. The fluids in the reservoirs were considered homogeneous throughout the experiment and changes in the cell configuration at two constant parameters were presented in the 2D plot control with the use of the MAPLE 18 software package. The study revealed the nature of the temperature distribution that the higher temperature distribution is obtained when heat is transferred from the first tank to the fifth tank and the reverse reaction occurs in all five reservoirs when ψ = 0.0025 and ω = 0.0025 respectively. Numerical results obtained are prototypes of oil temperature distribution performed under laboratory conditions in a thermodynamic experiment.